Capital and Collusion: The Political Logic of Global Economic Development - Baragar, Fletcher (Labour / Le Travail, 2007)
The article reviews the book, "Capital and Collusion: The Political Logic of Global Economic Development," by Hilton L. Root.
Keywords: BOOKS – Reviews; CAPITAL & Collusion: The Political Logic of Global Economic Development (Book); Nonfiction; ROOT; Hilton L.; economic development

Global Governance in Question: Empire, Class and the New Common Sense in Managing North-South Relations - Baragar, Fletcher (Labour / Le Travail, 2008)
The article reviews the book, "Global Governance in Question: Empire, Class and the New Common Sense in Managing North-South Relations," by Susanne Soederberg.
Keywords: BOOKS – Reviews; GLOBAL Governance in Question: Empire; Class & the New Common Sense in Managing North-South Relations (Book); International relations; Nonfiction; SOEDERBERG; Susanne

Marx's Wage Theory in Historical Perspective: Its Origins, Development, and Interpretation - Baragar, Fletcher (Labour / Le Travail, 1999)
The article reviews the book, "Marx's Wage Theory in Historical Perspective: Its Origins, Development, and Interpretation," by Kenneth Lapides.